Manufacturing and the product cycle a case study of Moran furniture - Collins, Cath.; Donato, Aaron Firth; Harding, Ben, producer/director/writer.; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2006)
"The development process for any product, large or small, is complex and made up of many phases. This program examines the various stages of manufacturing that take place in the production of an award-winning line of furniture. Viewers receive an in-depth look at the product cycle, from the initial concept to the evaluation of a finished sofa. At each stage, the program spotlights the personnel involved and the specialized roles they play in the process. Students gain an understanding of what goes into design, creation of the prototype, production, distribution, marketing, sales, evaluation, and modification."--Container.
Keywords: Furniture design; Furniture industry and trade -- Australia; Furniture making; Product life cycle; Product management